154k views
2 votes
Solve for x: z(14x−2y)=7 if z equals 0 Solve for x: z(14x−2y)=7 if z does not equal 0

1 Answer

4 votes

Answer:


  • z = 0; x doesn't have a solution

  • z\\eq 0;
    x = (1)/(14)((7)/(z) + 2y)

Explanation:

Given


z(14x -2y)=7

Required;

Solve for x, when


  • z = 0

  • z\\eq 0


z(14x -2y)=7

Divide both sides by z


(z(14x -2y))/(z) = (7)/(z)


14x -2y = (7)/(z)

Add 2y to both sides


14x -2y + 2y= (7)/(z) + 2y


14x = (7)/(z) + 2y

Divide both sides by 14


(14x)/(14) = (1)/(14)((7)/(z) + 2y)


x = (1)/(14)((7)/(z) + 2y)

The above expression is the value of x when
z\\eq 0

To solve for when z = 0, we simply substitute 0 for z


x = (1)/(14)((7)/(z) + 2y)


x = (1)/(14)((7)/(0) + 2y)

0 cant't divide any number; hence, from the above expression we conclude that


x = \ u\ n\ d\ e \ f\ i \ n\ e\ d

or

x doesn't have a solution

User NoNameZ
by
5.6k points